NILAI- NILAI KERUKUNAN DAN SALING MENGHARGAI DALAM PERSPEKTIF AL- QUR’AN: KAJIAN TEMATIK AYAT- AYAT SOSIAL - Salahuddin Harahap; Nuraisyah; Irfansyah; Itcat Martua Harahap (Wahdatul Ulum Institute, 2026)
This study examines the concept of harmony and the values of mutual respect in the social verses of the Qur’an. The study is motivated by the growing challenges of modern society, such as intolerance, discrimination, hate speech, and social conflict in multicultural communities. The objective of this study is to analyze the concept of harmony in the Qur’an and to explain the values of tolerance, brotherhood, social justice, and the prohibition against insulting others and harboring ill will in social life. The study employs a qualitative method using a literature review approach (library research). Data were obtained from the Qur’an, exegetical works, books, and relevant scientific journals, and were then analyzed using a descriptive-analytical approach. The results of the study indicate that the Qur’an establishes harmony as the foundation of social life through the reinforcement of the values of tolerance, brotherhood, justice, and respect for human dignity. These values are reflected in Surah An-Nahl verse 125, Surah Al-Hujurat verses 10–12, and Surah Al-Ma’idah verse 8. The social values in the Qur’an hold strong relevance in modern life as a guide for building a peaceful, harmonious, and mutually respectful society.